Impact test analysis of aluminum alloy wheels under different temperature - YAYLA, PAŞA (My University, 2023)
Aluminum alloy wheels are used worldwide in both the warmest and coldest temperatures. This study was conducted to investigate the impact resistance of aluminum alloy wheels produced by the low-pressure die casting process in real-life conditions. The V-notched Charpy impact test specimens were extracted from T6 heat-treated A356 aluminum alloy wheels. These specimens were tested with an instrumented Charpy V-notched impact tester after being conditioned at temperatures of - 75, - 40, 0, 20, 60, 95, and 175 degrees C. Charpy impact test diagrams of load-time and energy-time were created. The average crack initiation Charpy impact strength, average crack propagation Charpy impact strength, and average total Charpy impact strength values at different temperatures were calculated. Analysis of the fracture surfaces was performed using a scanning electron microscope (SEM), and the microstructure was analyzed using optical microscopy. In addition, the chemical characterization of the samples was performed by energy-dispersive spectroscopy (EDS) and optical emission spectroscopy (OES). The results of all the instrumented Charpy impact tests, together with the macroscopic and microscopic fracture surface examinations, revealed important results on the nature of fracture and the effects of different temperatures. The study revealed the variations of the Charpy crack initiation, crack propagation and total impact strengths as a function over a wide range of temperatures.
Keywords: Metalurji ve Malzeme Mühendisliği; Mühendislik ve Teknoloji; Metallurgical and Materials Engineering; Engineering and Technology; METALURJİ VE METALURJİ MÜHENDİSLİĞİ; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); METALLURGY & METALLURGICAL ENGINEERING; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Genel Malzeme Bilimi; Fizik Bilimleri; General Materials Science; Physical Sciences; aluminum alloys; instrumented Charpy impact strength; temperature effects; micro- and macrostructure; MECHANICAL-BEHAVIOR; AUTOMOTIVE WHEEL; A356 ALLOY; TOUGHNESS; MG; aluminum alloys; instrumented Charpy impact strength; temperature effects; micro- and macrostructure